2018
DOI: 10.3390/rs10111816
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Building and Infrastructure Instabilities by Automatic Spatiotemporal Analysis of Satellite SAR Interferometry Measurements

Abstract: Satellite synthetic aperture radar (SAR) interferometry (InSAR) is a powerful technology to monitor slow ground surface movements. However, the extraction and interpretation of information from big sets of InSAR measurements is a complex and demanding task. In this paper, a new method is presented for automatically detecting potential instability risks affecting buildings and infrastructures, by searching for anomalies in the persistent scatterer (PS) deformations, either in the spatial or in the temporal dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
(36 reference statements)
0
37
0
Order By: Relevance
“…Usually built on different fundaments as their surroundings, such infrastructures often present particular deformation patterns in comparison to their direct neighbourhood. Approaches for the automatic detection of such irregular patterns in space and time have been developed already (Zhu et al, 2018), few also considering the interaction between geology and observed subsidence (Pratesi et el., 2016;North et al, 2017). While some approaches rely principally on the velocity estimates for clustering (Kalia, 2018;Aslan, 2020), other approaches consider the time series of the displacements for identifying different deformation regimes (Zhu et al, 2018).…”
Section: State-of-the-artmentioning
confidence: 99%
“…Usually built on different fundaments as their surroundings, such infrastructures often present particular deformation patterns in comparison to their direct neighbourhood. Approaches for the automatic detection of such irregular patterns in space and time have been developed already (Zhu et al, 2018), few also considering the interaction between geology and observed subsidence (Pratesi et el., 2016;North et al, 2017). While some approaches rely principally on the velocity estimates for clustering (Kalia, 2018;Aslan, 2020), other approaches consider the time series of the displacements for identifying different deformation regimes (Zhu et al, 2018).…”
Section: State-of-the-artmentioning
confidence: 99%
“…While monitoring of individual infrastructure is critical, the regional-scale monitoring of infrastructure is hypercritical for land use planning and sustainable development. Studies have shown the application of satellite-based Interferometric Synthetic Aperture Radar (InSAR) for monitoring bridges and critical infrastructure as well as regional-scale displacement from tectonics and other processes [8][9][10][11][12]. This study builds on those efforts to demonstrate how InSAR based (particularly Persistent Scatterer Interferometry (PSI)) monitoring and Geographic Information System (GIS) based analysis can be helpful to understand the performance of an individual infrastructure as well as evaluate whether regional scale processes control these performances.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, in the presented study, we reprocessed the overall ascending and descending CSK dataset analyzed in [2] by exploiting two independent SAR processing techniques: the Small BAseline Subset (SBAS) [5][6][7] and the Advanced Tomographic SAR (TomoSAR) [8,9] approaches, respectively. These two methods are nowadays well-established tools for the investigation of the temporal evolution of displacements affecting buildings and infrastructures [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%